The Shift of Real Estate Development in India - Haritha, Karunamurthy (Journal of Progress in Civil Engineering, 2025)
Real Estate, a key pillar of the Indian economy, has seen remarkable growth in recent years, driven by new government regulations, evolving consumer preferences, and dynamic economic conditions. This paper explores emerging trends, including the rise in luxury real estate and challenges in affordable housing. One of the most notable trends that has emerged in the Indian real estate is the rise in demand for luxury real estate, which contrasts with the scarcity of middle - class inventories. The review of the economic reports and data reveals that India's residential real estate industry saw a huge upswing in FY23, with home sales values hitting an all - time high of Rs.3.47 lakh crore (US42 billion), representing a strong 48% YoY rise. According to the Economic Times Housing Finance Summit, with a population growing at a rate of 2.1% per year on average and the low purchasing power of a significant portion of our population, meeting the 40 million urban housing demands needs to be addressed. Secondary research reveals a strong growth trajectory for the sector, underscoring the need for collaboration among stakeholders to meet urban housing demands and achieve sustainability goals by 2030.